Development of a kit-like radiofluorinated biomolecule leading to a controlled self-assembly of 18F nanoparticles for a smart PET imaging application. Issue 48 (1st June 2017) - Lin, Jianguo; Wang, Wei; Li, Ke; Huang, Hongbo; Lv, Gaochao; Peng, Ying; Luo, Shineng; Qiu, Ling
Abstract : A kit-like radiofluorinated biomolecule was designed for convenient and precise PET imaging of biothiol levels in living subjects. Abstract : A kit-like 18 F-fluorination method has been successfully applied to prepare an activatable probe1 with good radiochemical yield and high specific activity. The probe has good in vitro stability and favorable cell membrane permeability. A controlled condensation reaction was initiated, and self-assembly into nanoparticles occurred when the probe was in a reducing environment. Positron emission tomography (PET) imaging of the biothiol level in living subjects was conveniently and precisely realized using this probe. The present study may provide a new platform for the development of "smart" PET tracers for tumor imaging.